PELAKSANAAN SUPERVISI OLEH KEPALA SEKOLAH DAN PENGAWAS SEKOLAH - Nurfatah, Nurfatah; Rahmad, Nur (Graduate Program Magister Manajemen Pendidikan, 2018)
Technical assistance is provided to teachers as an ongoing capacity building effort. The assistance is in the form of academic supervision by principals and school supervisors. The school supervisor also does managerial supervision to the principal. This research is a qualitative research with case study. The research was conducted at SDN 8 Talang kelapa. The result of the research was the supervision of principal and school supervisor has made better performance of teacher. It was seen from the good preparation of learning equipment. While the implementation of learning has not been completely good because it still uses the old methods such as lecturing and assignments. There were still 15% of teachers who nervous when it will be supervised, this caused by several factors 1) teachers who are almost retired, an average age of 55 years and above; 2) teachers who lack the computer. The difference between principal supervision and supervision of school supervisors lies in subjects supervised, implementation schedule, and follow-up.